CFTR interactome mapping using the mammalian membrane two‐hybrid high‐throughput screening system. Issue 2 (14th February 2022) - Lim, Sang Hyun; Snider, Jamie; Birimberg‐Schwartz, Liron; Ip, Wan; Serralha, Joana C; Botelho, Hugo M; Lopes‐Pacheco, Miquéias; Pinto, Madalena C; Moutaoufik, Mohamed Taha; Zilocchi, Mara; Laselva, Onofrio; Esmaeili, Mohsen; et al.
Abstract: Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) is a chloride and bicarbonate channel in secretory epithelia with a critical role in maintaining fluid homeostasis. Mutations in CFTR are associated with Cystic Fibrosis (CF), the most common lethal autosomal recessive disorder in Caucasians. While remarkable treatment advances have been made recently in the form of modulator drugs directly rescuing CFTR dysfunction, there is still considerable scope for improvement of therapeutic effectiveness. Here, we report the application of a high‐throughput screening variant of the Mammalian Membrane Two‐Hybrid (MaMTH‐HTS) to map the protein–protein interactions of wild‐type (wt) and mutant CFTR (F508del), in an effort to better understand CF cellular effects and identify new drug targets for patient‐specific treatments. Combined with functional validation in multiple disease models, we have uncovered candidate proteins with potential roles in CFTR function/CF pathophysiology, including Fibrinogen Like 2 (FGL2), which we demonstrate in patient‐derived intestinal organoids has a significant effect on CFTR functional expression. SYNOPSIS: A new MaMTH‐HTS platform is used with a Human ORFeome library to map the protein‐protein interactions of full‐length wildtype and F508del CFTR. Functional validations in multiple disease models uncovered proteins with potential roles in CFTR function and cystic fibrosis. MaMTH‐HTS identifies 447 interactors of wildtype and F508del CFTR. The CFTR interactomes are evaluated using traditional MaMTH and a fluorescence‐based assay is performed to monitor the effect of transiently expressed interactors on CFTR channel activity. siRNA‐mediated knockdown of candidate proteins reveals 19 interactors whose down‐regulation led to increased F508del CFTR trafficking and complex glycosylation. One candidate protein, Fibrinogen Like 2 (FGL2) has a significant effect on CFTR functional expression, as demonstrated in patient‐derived intestinal organoids. Abstract : A new MaMTH‐HTS platform is used with a Human ORFeome library to map the protein‐protein interactions of full‐length wildtype and F508del CFTR. Functional validations in multiple disease models uncovered proteins with potential roles in CFTR function and cystic fibrosis.